Model Bangkitan dan Karakteristik Perjalanan pada Perumahan Kelapa Gading Kalukubula Kecamatan Sigi Biromaru - Koswanto , R.H.; Ramlan, R.; Setiawan, A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Increasing population density will affect land use into residential/community housing areas and the emergence of settlements will increase the number of movements generated which can disrupt traffic flow which then reduces the level of road service. This research aims to model the generation of movement in the Kelapa Gading Kalukubula housing area and to determine the amount of traffic generation in the housing at present and in the future because the housing will continue to develop and will analyze the factors that influence the generation of traffic movement. Data collection was carried out by filling out a questionnaire which was distributed and given to residents using a sampling technique (stratified random sampling). To produce a good generation model based on ordinary less squares (OLS), the results of the questionnaire are processed and analyzed using multiple linear regression by SPSS software. Socio-economic characteristics and travel characteristics of the occupants of the house are tabulated as factors influencing the value of trip generation at Kelapa Gading Kalukubula Housing. The best model for generating movement in the Kelapa Gading Kalukubula housing complex is Y = -0.584 + 0.168 X1 + 0.349 X2 + 0.366 X3 + 0.092 X4 + 0.212 X5 with R2 = 0.695, F falue 159.138 where is X1 amount of family member, X2 is amount of worker in family member, X3 is amount of students in family, X4 is amount of car ownership, X5 is amount of motorbike ownership. Based on this model, the total trip generation is 8289 trips/day and averange of trips is 3 trips/day, while the vehicle leaving housing from the Traffic Count is 9462 trips/day and vehicles entering the housing is 10397 trips/day